MAINTAINING THE STABILITY OF TIGHTENING OF BOLT JOINTS IN THE PRESENCE OF ORGANIC FILMS - Бивойно, Т. П.; Лабунець, В. Ф.; Дерек, І. Б. (Proceedings of National Aviation University (archive), 2021)
The tension of pre-tightening of threaded joints is considered. Practical recommendations for prevention of reduction of the moment of unscrewing of threaded connections without use of locking elements are offered.